2008
DOI: 10.1590/s0004-282x2008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Familial cerebral cavernous malformations: Rio de Janeiro study and review of the recommendations for management

Abstract: -Objective: Multiple cerebral cavernous malformation (CCM) is the hallmark of familial presentation of cavernous malformation in the brain. We describe an ongoing Familial Cerebral Cavernous Malformation Project in the Rio de Janeiro state showing genetic profile and the pattern of emergent neuroimaging findings of this particular population besides a review of the updated recommendations for management of familial CCM versus patients harboring sporadic lesions. Method: Four families of our cohort of 9 familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…The CCM2 L113P mutation was reported in a patient by Riant et al (12), but the clinical significance of this mutation was listed as unknown. Similarly, the KRIT1 L238F mutation was previously reported in one family (42). Finally, the pathogenic mechanism of the KRIT1 D281G mutation was reported to be through the introduction of a new, alternative splice donor site (14).…”
Section: Methodsmentioning
confidence: 57%
“…The CCM2 L113P mutation was reported in a patient by Riant et al (12), but the clinical significance of this mutation was listed as unknown. Similarly, the KRIT1 L238F mutation was previously reported in one family (42). Finally, the pathogenic mechanism of the KRIT1 D281G mutation was reported to be through the introduction of a new, alternative splice donor site (14).…”
Section: Methodsmentioning
confidence: 57%
“…In an ongoing study for a Register of Disease for Cerebral Cavernomas in Brazil, the CCM cohort at the Federal University of Rio Janeiro has also detected the predominance of CCM1 mutational profile in the studied families 21 . In another multicenter study it was reported a very aggressive profile of FCCM cases due to mutations of the gene CCM3 22 , with a mean age at presentation of 12 years and an excessive lesion burden, meaning 33% of the patients having more than 100 lesions and 78% with more than 20 lesions.…”
Section: Familial Cerebral Cavernous Malformations (Fccm)mentioning
confidence: 88%
“…No exame de tomografia as lesões são vistas como de alta densidade, pois os sangramentos são agudos, já na ressonância magnética aparecem como imagens de sangramento recente intra ou perilesionais. ( DOMINGUES et al 2008) Durante o estudo observa-se que a genética familiar é responsável por 30 a 50% dos casos, e que a maioria dos cavernomas familiares tem mais de uma lesão, é caracterizada por ser uma doença autossômica dominante com penetrância variável e mutações levando a perda…”
Section: Conclusãounclassified
“…A Malformação Cavernosa Múltipla Familiar constitui uma síndrome com padrão de herança autossômica dominante, que se caracteriza pela formação de hamartomas vasculares no sistema nervoso central e se relaciona principalmente a mutações nos genes CCM tipo 1, tipo 2 e tipo 3, sendo o primeiro o mais comum (DOMINGUES et al, 2008;MIRANDA et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation